Dimensões da alfabetização científica na formação inicial de professores de química - Leite, Rosana Franzen (2015)
Scientific literacy (SL) is a goal for the twenty-first century. This theme has been the focus of studies and research that influence the initial and continuing education of natural science teachers. Various terms and concepts can be found in the literature as regards this subject. SL dimensions for the initial education of chemistry teachers are proposed here: a) understanding of the nature of science and scientific knowledge; b) identification and recognition of the importance of concepts and scientific theories in daily processes; c) clarity of the socioscientific aspects involved in diverse situations of life. This proposal is supported by references such as Laugksch and Carvalho, which consist of important reviews about SL terms and concepts. They are, mainly, Millar, Cachapuz et al., Santos, Sanmartí, Gil Perez et al., Sasseron and Carvalho and Auler and Delizoicov. The present work seeks a connection between them, in order to produce new meanings concerned with teacher education. It also attempts to bring to this connection ideas related to teacher education from Maldaner Carvalho and Gil-Pérez and Pimenta. Considering investigations about the development of the scientific literacy process in a school environment extremely relevant, this work aimed to examine how a course to train chemistry teachers contributed to the scientific literacy of its students, as citizens and future teachers. Fifty-one chemistry students from a Paraná state university, taking the above-mentioned course, answered a questionnaire, were interviewed (semi-structured) and produced narratives. Student ideas about science, the scientist and scientific work emerged from the data analysis. These ideas were simplistic and popular, which also implies the non-recognition of other aspects related to scientific activities (e.g. socioscientific). In relation to environmental questions, nothing much beyond romantic and awareness-based ideas was identified, and even this would be considered the role of the school. Moreover, it was possible to identify an absence of reflection regarding the knowledge to be taught in the school, which reveals one of the gaps in this educational stage, mainly referring to the transformations that the knowledge undergoes before entering the classroom. Thus, the student teachers are involved in well-defined concepts that are considered pure by the specific-content disciplines of the course; whereas the disciplines of the teaching area demonstrate concern with wider discussions, considering socioscientific themes and epistemological questions. The present study also showed the necessity to rethink the initial education courses of chemistry teachers, with a view to the insertion of the students into a scientific culture that can be guided by the incorporation of the SL dimensions proposed here, not only the profile of the professional described in official documents, but also the routine of these courses, letting them choose the organizational form.